The Dynamic of Consumer Trust and Ease of Use in Online Travel Booking: A Comparative Study - Himmatul Syahriyanti; Mariaton Sa’diyah; Ayu Rosita Anggraini (JURNAL PENDIDIKAN IPS, 2024)
Currently, Indonesia's digital economy reaches Rp 391 trillion, with a contribution of 49%. The most popular online purchase plan in Indonesia is Travelling. Traveloka.com is an example of e-commerce that allows customers to find flight tickets from various airlines. The high level of business competition and technological advancements currently impact the progress of the service industry, which has become more practical by integrating application-based technology with transportation services. This study aims to compare the influence of trust and convenience on the purchase of airline tickets through Traveloka.com and other e-commerce platforms. In addition, this study also examines the differences in the effects of these two variables on undergraduate and postgraduate students at the Faculty of Economics, UIN Maulana Malik Ibrahim. This study uses a quantitative approach with multiple linear regression analysis methods and data processing through the SPSS 25 program. The research results show that trust has no influence and is not significant on Purchase Decisions, as evidenced by the t-statistic test result < t-table (1.548< 1.99912) and a non-significant value (0.126>0.05). Ease of use has an influence and is significant on Purchase Decisions, as evidenced by the t-statistic value > t-table (8.623>1.9912) and a significant value of 0.000<0.05. The research results are expected to provide an overview of consumer preferences in purchasing airline tickets based on trust and comfort levels, as well as differences in preferences based on respondent groups.